We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
40
1
avatar

http://prntscr.com/mboif9

 Jan 24, 2019

Best Answer 

 #1
avatar+18017 
+1

6^(-10) / 6^(-4)  =  6^(-10 -(-4))  = 6 ^(-6)

 Jan 24, 2019
 #1
avatar+18017 
+1
Best Answer

6^(-10) / 6^(-4)  =  6^(-10 -(-4))  = 6 ^(-6)

ElectricPavlov Jan 24, 2019

25 Online Users

avatar
avatar
avatar